Correction: Absence of posterior pituitary bright spot in adults with CNS tuberculosis: A case-control study. - Smitesh Gutta; Pavithra Mannam; Vignesh Kumar; Tina George; Murugabharathy K; Turaka Vijay Prakash; Bijesh Yadav; Thambu David Sudarsanam (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0275460.].